2013
DOI: 10.1002/we.1656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the preload in the general static load‐carrying capacity of four‐contact‐point slewing bearings for wind turbine generators: theoretical model and finite element calculations

Abstract: This paper presents a generalization of previous works developed by the authors in the field of the calculation and selection of slewing bearings, where a theoretical model for the estimation of the static load-carrying capacity of four-contact-point slewing bearings was obtained. Those previous works assumed that there was no preload in the balls; in the present work, the model has been improved in order to consider the effect of the preload, in such a way that it provides more realistic results because this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Figure compares the results for rigid and deformable rings to demonstrate the effect of the flexibility of the rings on the bearing stiffness. The results for rigid rings were obtained through the analytical model by the authors . From the figure, it is concluded that rigid ring assumption largely overestimates the stiffness of the bearing, especially for large bearings.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Figure compares the results for rigid and deformable rings to demonstrate the effect of the flexibility of the rings on the bearing stiffness. The results for rigid rings were obtained through the analytical model by the authors . From the figure, it is concluded that rigid ring assumption largely overestimates the stiffness of the bearing, especially for large bearings.…”
Section: Resultsmentioning
confidence: 98%
“…The aim of decoupling the problem was to consider separately the effect of the different parameters on the stiffness. By doing this, contact parameters such as ball preload or conformity ratio only affect δ contact as described in the analytical model by the authors . On the other hand, δ rings is affected by the rest of the geometrical parameters, being D w and D pw the main ones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations